An efficient hybrid model for secure transmission of data by using efficient data collection and dissemination (EDCD) algorithm based WSN - Mustafa Mahmood Akawee; Mohanad Ali Meteab Al-Obaidi; Haider Mohammed Turki Al-Hilfi; Sabbar Insaif Jassim; Tole Sutikno (Institute of Advanced Engineering and Science, 2020)
Wireless sensor network (WSN) is one of the most important elements of the Internet of Things paradigm. Energy consumption is a vital issue in IoT and WSN. Security primitives in the IoT are energy consuming. Addressed the security issue for transmitted data by IoT sensor node add another challenge in term of energy consumption. finding the satisfactory solutions that reduce power consumption at the same time as making sure the required security services is not always an easy undertaking. Therefore, in this article, we proposed an efficient hybrid model for secure transmission of data from sensor nodes to receivers in WSN applications. The proposed model includes two algorithms rivest–shamir–adleman (RSA) and efficient data collection and dissemination (EDCD). The key idea behind the proposed model is to prevent to secure sensed data if no significant change between the current data and the last transmitted data by the apply EDCD1 algorithm, which that will help in saving the sensor node energy. The reason for that the size of cipher data is so large compared to the sensed data, which that will increase the energy consumption. The outcome results shown that the proposed model has a high performance compared to RSA in term of energy consumption.